Enantioselective Synthesis of (2S, 3S)‐epi‐Oxetin and Its Incorporation into Conformationally Constrained Pyrrolidinyl PNA with an Oxetane Backbone. Issue 5 (16th February 2017) - Seankongsuk, Pattarakiat; Vchirawongkwin, Viwat; Bates, Roderick W.; Padungros, Panuwat; Vilaivan, Tirayut
Abstract: Fmoc‐protected (2 S, 3 S )‐ epi ‐oxetin was synthesized from ( E )‐4‐(benzyloxy)but‐2‐enal via enantioselective organocatalytic epoxidation, epoxide ring opening with azide, alcohol activation and ring closure, followed by functional‐group manipulation in eight steps with 12 % overall yield and 94 %  ee . The amino acid was used as a building block for a new conformationally constrained pyrrolidinyl PNA with an oxetane‐containing backbone. The unexpected sensitivity of the oxetane backbone posed considerable synthetic challenges under standard Fmoc‐solid‐phase peptide synthesis conditions, and a mechanism for acid‐catalyzed degradation was proposed. In addition, the DNA‐ and RNA‐binding properties of the oxetane PNA were investigated. The presence of an oxetane ring decreased the stability of the PNA⋅ DNA and PNA⋅ RNA duplexes when compared to PNA with a cyclobutane‐containing backbone, which could be explained by the flattening of the oxetane ring, leading to a suboptimal torsional angle. Abstract : (2 S, 3 S )‐Fmoc‐ epi ‐oxetin was synthesized by an eight‐step reaction sequence in 12 % overall yield and 94 %  ee and was used as a key building block to synthesize a new pyrrolidinyl PNA (aocPNA). The presence of an oxetane ring decreased the stability of PNA⋅ DNA and PNA⋅ RNA duplexes when compared to the cyclobutane analogue, which could be explained by the larger torsional angle of the oxetane amino acid compared to the cyclobutane amino acid.